2008
DOI: 10.3174/ajnr.a1322
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Xerostomia: Objective Evaluation of Salivary Gland Injury Using MR Sialography

Abstract: BACKGROUND AND PURPOSE: Xerostomia (dry mouth) is one of the serious complications of head and neck irradiation and has a strong influence on a patient's activities of daily living. MR sialography with salivary secretion stimulation provides additional functional information (salivary secretion reserve) and may contribute to the evaluation of the severity of xerostomia and predict the risk of developing a radiation-induced xerostomia. This aim of the study was to analyze MR sialography as an objective tool to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 19 publications
3
21
0
1
Order By: Relevance
“…The protective effect of KRG on the salivary gland represents an additional benefit of KRG administration for oral mucositis, because damage to the salivary gland results in decreased salivation and can make the oral mucosa more vulnerable to radiation-induced injury (15,16,25,26). Recent study suggested that SMG is associated with prevention of radiation damage to murine tongue epithelial cells, an effect of saliva; this supports our findings (27).…”
Section: Discussionsupporting
confidence: 88%
“…The protective effect of KRG on the salivary gland represents an additional benefit of KRG administration for oral mucositis, because damage to the salivary gland results in decreased salivation and can make the oral mucosa more vulnerable to radiation-induced injury (15,16,25,26). Recent study suggested that SMG is associated with prevention of radiation damage to murine tongue epithelial cells, an effect of saliva; this supports our findings (27).…”
Section: Discussionsupporting
confidence: 88%
“…The smaller size of parotid glands found in post-RT NPC patients was due to acinar cell loss and acinar atrophy after irradiation (Henriksson et al 1994;Radfar and Sirois 2003). Volume reduction of parotid glands after radiotherapy had been documented in previous studies using computed tomography (CT) (Barker et al 2004;Lee et al 2008) and magnetic resonance imaging (MRI) (Nomayr et al 2001;Wada et al 2009). Nevertheless, the result of the present study only showed significant difference in the mean transverse dimension of the glands among the three study groups but not in the mean longitudinal dimension, which was consistent with the finding of our pilot study (Ying et al 2007).…”
Section: Discussionmentioning
confidence: 89%
“…2). 9 Three grades were used to evaluate gland volumes: grade 1 = normal; grade 2 = gland swelling (larger than normal); and grade 3 = gland atrophy (smaller than normal).…”
Section: Interpretation Of Mr Sialography Findingsmentioning
confidence: 99%